Beyond Style and Genre - Jost, Christofer (Waxmann, 2023)
Popular culture today manifests itself in a dense network of styles and genres, while the aesthetic preferences of the audience are highly differentiated. Besides, popular culture also implies a diversity of aesthetic strategies, discourses and value systems that traverse the symbolic demarcations between styles and genres and are effective across different artistic fields and individual media. Aesthetic concepts such as camp, retro or trash are expressions of a transgressive mode of production that facilitates a multitude of cross-connections between aesthetic spaces of experience. The volume brings together authors from different disciplines who approach aesthetic concepts in popular culture on a historical, theoretical and methodological level, analyze them on the basis of various aesthetic phenomena, or discuss aspects relevant to their theoretical contextualization, such as the emergence and establishment of artistic practices and aesthetic value systems.
Keywords: Popkultur; Popmusik; Ästhetik; Popular culture; Popular aesthetics; aesthetic theory; jazz; reggae; dancehall; avant-garde; MAD; camp; pop; ostalgia; german cinema; queerness; wabi sabi; theater; space disco; electronic music; cold pop; german country music; Urban Explorers